Optimum plot size for oil palm (Elaeis guineensis Jacq.) field experiments: OPTIMUM PLOT SIZE FOR OIL PALM FIELD EXPERIMENTS - MANORAMA KAMIREDDY; CHANDRAN K P; RAVI KUMAR MATHUR; KANCHERLA SURESH; SANJIB KUMAR BEHERA (Journal of Oilseeds Research, 2019)
For standardization of water and nutrient requirements of oil palm field experimentation is essential. In order to get accurate results from the field experimentation, optimal plot size is very important. Not much work has been done on these lines to find out the optimum size of the plot for field experimentation in oil palm. In the present study, two statistical methods were employed and compared to find out the optimal plot size for conducting field experiments in oil palm under Indian conditions using 6 years yield data from ICAR-Indian Institute of Oil palm Research. Oil palm yield is measured in FFBs (fresh fruit bunches) and the FFB number and yield data of individual palms was collected from 10 different cross combinations having three replications and 270 palms. Two statistical procedures were employed on these data viz., Mean Square Error (MSE) and Maximum curvature method. From both these methods, 7 palms per plot were found to be the optimum size in oil palm for field experiments. As both MSE and maximum curvature of coefficient of variation methods have given same result, if secondary data is available for any other tree crops, one of these two methods can be employed for finding out the optimum plot size.